Oktoberfest . Octoberfest - Kresoja, Dragan (Inex Film Beograd, 1987)
This social drama set in the late 1980s Belgrade focuses on dreamy youngster Luka Banjanin Lule whose main ambition is to visit the Munich beer “Octoberfest.” Together with his unemployed friends he hangs out at the usual youth meeting places, seemingly happy. But Lule is actually haunted by a small sin from his past. When he was still at high school, two drug dealers offered him a substantial sum of money to smuggle a small amount of drugs across the state border and, unfortunately, he was caught. Now, all he does is dream of leaving his home and changing his monotonous, restricted life, but this small crime constantly preoccupies him. Not only has his passport been taken away, but ever since the incident happened he has been constantly harassed by the police, especially by a chief inspector who cannot forget Lule’s mistake. All kinds of images from his grim life interlace with idyllic dreams of this ultimate foreign event – the Octoberfest. In search of a new life and growing up, friends gradually part and Lule chooses a harrowing, but tempting path of crime. Eventually, a glint of hope appears when his passport is returned. The only problem is that it is too late.